2019
DOI: 10.3389/fpsyg.2019.01363
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reliability of the Framework for Equitable and Effective Teaching With the Many-Facet Rasch Model

Abstract: This manuscript reports results of an empirical assessment of a newly developed measure designed to assess apprentice teaching proficiency. In this study, Many Facets Rasch model software was used to evaluate the psychometric quality of the Framework for Equitable and Effective Teaching (FEET), a rater-mediated assessment. The analysis focused on examining variability in (1) supervisor severity in ratings, (2) level of item difficulty, (3) time of assessment, and (4) teacher apprentice proficiency. Added valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Unlike widely-used models of teacher evaluation, which are centered in whiteness and dominant culture, FEET deliberately integrates equity language and concepts into all levels of teaching, including engaging students, planning, teaching equitably, and exemplifying leadership (Salazar, 2018; Salazar & Lerner, 2019). In speaking to us about the FEET at DU, Salazar emphasized that the framework is not only research- and standards-based (Govindasamy et al, 2019; Salazar, 2018) but also draws on a long history of the work of scholars of color and the values of minoritized communities, including her own experiences as a Latinx schoolchild whose culture and knowledge were excluded from the curriculum (M. Salazar, personal communication, December 1, 2021). The development of the FEET involved a 10-year pilot period at DU, which showed that teacher candidates prepared according to the guidelines of the framework were effective in the classroom.…”
Section: Equity-centered Teacher Education Evaluation: Promising Poli...mentioning
confidence: 99%
“…Unlike widely-used models of teacher evaluation, which are centered in whiteness and dominant culture, FEET deliberately integrates equity language and concepts into all levels of teaching, including engaging students, planning, teaching equitably, and exemplifying leadership (Salazar, 2018; Salazar & Lerner, 2019). In speaking to us about the FEET at DU, Salazar emphasized that the framework is not only research- and standards-based (Govindasamy et al, 2019; Salazar, 2018) but also draws on a long history of the work of scholars of color and the values of minoritized communities, including her own experiences as a Latinx schoolchild whose culture and knowledge were excluded from the curriculum (M. Salazar, personal communication, December 1, 2021). The development of the FEET involved a 10-year pilot period at DU, which showed that teacher candidates prepared according to the guidelines of the framework were effective in the classroom.…”
Section: Equity-centered Teacher Education Evaluation: Promising Poli...mentioning
confidence: 99%
“…other than individual and item facets. MFRM is a measurement model that can overcome the limitations of Classical Test Theory (CTT) (Anshel et al, 2009;Kim et al, 2012;Govindasamy et al, 2019;Uto, 2020 ). In the MFRM, predictions for each facet (individual, item, rater, situation, etc.)…”
Section: Many Facet Rasch Modelmentioning
confidence: 99%
“…In another example, Tavakol and Pinner (2019) established four facets (students, examiners, fields, and stations) using MFRM to perform a more complex analysis of the quality of structured clinical examinations. Currently, MFRM is considered a more effective assessment method and is used in structured interviews, language-proficiency assessment and evaluation-scale development and verification, and for other purposes (Aryadoust et al, 2021; Govindasamy et al, 2019; McLaughlin et al, 2017; Young, 2019).…”
Section: Introductionmentioning
confidence: 99%